3F.005 The epidemiology of home and workplace injuries in Nepal: a household survey. (14th March 2021) - Deave, Toity; Pant, Puspa; Manandhar, Sunil Raja; Adhikari, Drubha; Joshi, Elisha; Joshi, Sunil; Mytton, Julie
Abstract : Background: Unintentional Injuries comprise the fifth leading cause of death in Nepal in 2017, an increase of 23% compared to 1990. In Nepal, there is minimal community-derived evidence of home or occupational injuries. Our aim was to describe the epidemiology of injuries in the Makwanpur district, including the causes and risk factors associated with those injuries. Methods: A cross-sectional, household survey was undertaken in three administrative areas of Nepal between April-June, 2019. Data were collected electronically about non-fatal and fatal injuries in the previous three months and five years, respectively. Results: 17, 593 individuals from 3, 327 households were surveyed; 394 people were injured. 136/394 (34.5%) injuries occurred in homes, 109 (27.7%) were work-related. 225 (55.8%) were males, the age range was 0–87 years, 123 (30.7%) were child injuries, (0–17 yrs). The most commonly reported injury was falls (n=173, 43.9%), stumbling and tripping were the most common reasons and 73 (42.2%) occurred at home. More injuries occurred in rural administrative areas than urban areas, especially occupational injuries (occupational: chi-square=22.05, p=0.000; home: chi-square=13.89, p<0.001). Conclusions: Home and occupational fall injuries are common, especially in rural areas. Understanding the context of falls, especially identifying and working with particular occupational groups where they are prevalent, may identify risk factors and help target messages about primary falls prevention and interventions. Learning Outcomes: Using hand-held computers and local enumerators for data collection in sample areas resulted in minimal missing data and monitoring of data quality during the collection period.